Penalaran Matematis Siswa SMA dalam Menyelesaikan Masalah Berdasarkan Kemampuan Matematika - Yulinah, Yulinah; Maf'ulah, Syarifatul; Nurwiani, Nurwiani (Universitas Dr. Soetomo, 2025)
Abstract Mathematical reasoning is a mental activity that connects relevant facts to draw conclusions based on valid arguments. This research aims to describe the mathematical reasoning of high school students with high, medium, and low mathematical abilities in solving problems. This research also offers a comprehensive understanding of how varying levels of mathematical ability influence students' reasoning processes in problem-solving. This research used qualitative methods with the subjects being three students in class X-8 of SMA Negeri 1 Trawas, each representing high, medium, and low levels of mathematical ability. Research instruments include mathematical ability tests, mathematical reasoning tests, and interview guidelines, with triangulation of time to ensure the validity of data. Data analysis was carried out through reduction, presentation, and concluding data. The research results show that students with high mathematical abilities can explain information in verbal and symbolic form, develop problem-solving strategies, carry out mathematical manipulations, provide reasons for solutions, check the correctness of each stage, and provide conclusions on the solution process. Students with moderate abilities show similar abilities but do not provide conclusions about the solution process. Meanwhile, students with low abilities also showed similar solution steps but did not provide conclusions about the solution process. These findings provide insight into differences in students' mathematical reasoning abilities based on their mathematical ability. Keywords: Mathematical Reasoning; Mathematical Ability; Solving Problems. Abstrak Penalaran matematis adalah aktivitas mental yang menghubungkan fakta-fakta relevan untuk menarik kesimpulan berdasarkan argumen yang valid. Penelitian ini bertujuan untuk mendeskripsikan penalaran matematis siswa SMA dengan kemampuan matematika tinggi, sedang, dan rendah dalam menyelesaikan masalah. Penelitian ini juga memberikan pemahaman yang komprehensif mengenai bagaimana tingkat kemampuan matematika memengaruhi proses penalaran siswa dalam menyelesaikan masalah. Penelitian ini menggunakan metode kualitatif dengan subjek tiga siswa kelas X-8 SMA Negeri 1 Trawas, masing-masing mewakili tingkat kemampuan matematika tinggi, sedang, dan rendah. Instrumen penelitian meliputi tes kemampuan matematika, tes penalaran matematis, dan pedoman wawancara, dengan triangulasi waktu untuk menjamin keabsahan data. Analisis data dilakukan melalui reduksi, pemaparan, dan penarikan kesimpulan dari data. Hasil penelitian menunjukkan bahwa siswa berkemampuan matematika tinggi mampu menjelaskan informasi dalam bentuk verbal dan simbol, menyusun strategi penyelesaian masalah, melakukan manipulasi matematika, memberikan alasan terhadap solusi yang diberikan, memeriksa kebenaran setiap tahapan, dan memberikan kesimpulan atas proses penyelesaian. Siswa berkemampuan sedang menunjukkan kemampuan serupa, tetapi tidak memberikan kesimpulan atas proses penyelesaian. Sementara itu, siswa berkemampuan rendah juga menunjukkan langkah-langkah penyelesaian serupa, namun tidak memberikan kesimpulan atas proses penyelesaian. Temuan ini memberikan wawasan mengenai perbedaan kemampuan penalaran matematis siswa berdasarkan kemampuan matematika. Kata Kunci:Menyelesaikan Masalah; Kemampuan Matematika; Penalaran Matematis.